Graphene–polymer coating for the realization of strain sensors - Bonavolontà, Carmela; Aramo, Carla; Valentino, Massimo; Pepe, Giampiero; De Nicola, Sergio; Carotenuto, Gianfranco; Longo, Angela; Palomba, Mariano; Boccardi, Simone; Meola, Carosena (Beilstein Journal of Nanotechnology, 2017)
In this work we present a novel route to produce a graphene-based film on a polymer substrate. A transparent graphite colloidal suspension was applied to a slat of poly(methyl methacrylate) (PMMA). The good adhesion to the PMMA surface, combined with the shear stress, allows a uniform and continuous spreading of the graphite nanocrystals, resulting in a very uniform graphene multilayer coating on the substrate surface. The fabrication process is simple and yields thin coatings characterized by high optical transparency and large electrical piezoresitivity. Such properties envisage potential applications of this polymer-supported coating for use in strain sensing. The electrical and mechanical properties of these PMMA/graphene coatings were characterized by bending tests. The electrical transport was investigated as a function of the applied stress. The structural and strain properties of the polymer composite material were studied under stress by infrared thermography and micro-Raman spectroscopy.
Keywords: graphene; graphite; IR thermography; micro-Raman spectroscopy; strain sensor